Scientific Communication Practices, Theories, and Pedagogies - Yu, Han; Northcut, Kathryn M. (Routledge Studies in Technical Communication, Rhetoric, and Culture, 2018)
This book addresses the roles and challenges of people who communicate science, who work with scientists, and who teach STEM majors how to write. In terms of practice and theory, chapters address themes encountered by scientists and communicators, including ethical challenges, visual displays, and communication with publics, as well as changed and changing contexts and genres. The pedagogy section covers topics important to instructors' everyday teaching as well as longer-term curricular development. Chapters address delivery of rhetorically informed instruction, communication from experts to the publics, writing assessment, online teaching, and communication-intensive pedagogies and curricula.